Synthesis of New Structural Analogues of Natural Integrastatins with a Basic Epoxybenzo[7,8]oxocine Skeleton: Combined Experimental and Computational Study - Stalinskaya, Alena L.; Chikunov, Semyon Y.; Pustolaikina, Irina A.; Gatilov, Yuri V.; Kulakov, Ivan V. (Synthesis, 2023)
In this work, the cyclization reactivity of various 3-acetyl-2-methylpyridines (including 3-acetyl-2-methylquinoline) containing both electron donor and acceptor substituents with salicylaldehyde into epoxybenzooxocino[4,3-b]pyridine derivatives was studied. The reactions were carried out in mild (under room temperature or reflux in 2-propanol) and harsh (in a sealed glass ampoule) conditions. It was shown that 3-acetyl-2-methylpyridines with an aryl substituent in the 4-position do not react with salicylaldehyde either under normal convection heating conditions or under more severe conditions. This effect was explained by the steric hindrance of the substituents using quantum chemical calculations. It was found that electron donor substituents in 3-acetyl-2-methylpyridines significantly facilitate cyclization in epoxybenzooxocino[4,3-b]pyridines. The presence of electron acceptor substituents (NO2 group for example) in the 5-position of pyridine prevents cyclization under normal conditions, but gives a rather high conversion to oxocinopyridines under more specific conditions. This effect is quantum-chemically explained by the decrease in the basicity of pyridine. Pyridines with two pairs of methyl groups in ortho-positions to the acetyl group are capable to form mixtures of regioisomeric epoxybenzooxocinopyridines. Further, epoxybenzooxocinopyridines with methyl and acetyl groups can form a mixture of diastereomeric bisoxocins under more specific conditions. All 17 initial pyridines were studied quantum-chemically in order to understand what features of their structure and properties affect the success of the cyclization reaction and the yield of the target product. The pyridine molecules were calculated by the DFT RB3LYP/6-311++G(d,p) method taking into account the alcohol solvent within the CPCM model using Gaussian-2016 program. It was shown that the absence of steric hindrances in the form of bulky substituents in 4-position of pyridines is the main factor affecting the success of the cyclization reaction. Also, the yield of the target product is affected by the CH-acidity of the methyl group in 2-position, which, in turn, is affected by electron-donating and electron-withdrawing substituents in the 5- and 6-positions.
Keywords: integrastatins A,B; intramolecular cyclization; tetracyclic epoxybenzooxocine; 3-acetyl-2-methylpyridine; computational study